SEMANTIC DEVELOPMENT THROUGH METAPHOR IN THE BOOK MEANINGS OF THE QUR’AN AND ITS PARSING BY AL-ZAJJAJ - Saddam Sami Jawad AL-Alwani (American Journals Publishing, 2023)
The Quran is the message of life as comprehensive as life itself, and every study in the Arabic language does not bear fruit unless it is connected to the Holy Quran; which is closely related to human life. The words of the Quran are the essence of the Arabic language, and its medium and honor, and upon them rely the scholars, jurists, and wise men in their judgments and rulings, and to them the poets and orators resort in their poetry and prose. Researching the significance of the words of the Quran and their development is considered one of the most enjoyable researches, due to the mental efforts and the retrieval of all the uses of the word from memory, and the difficulty in studying at this level, to understand the noble meanings intended by the holy text. The interpretations give the general meaning of the word or ready-made meanings, often not deeply rooted in the origin of the word and its development. Whatever the development of the meanings of the words, there must be some kind of relationship between the original meaning and the new meaning, and the most important of these relationships is the relationship of similarity in something. Perhaps this is what encouraged me to embark on this blessed field in Quranic linguistic studies, so we made the research sample; the Quranic words that Al-Zajjaj stopped at and hinted at their development through metaphor in his book "The Meanings and Grammar of the Quran", for two reasons: The fact that Al-Zajjaj's book represents the pinnacle of the maturity of the books of the meanings of the Quran, which represents the first threshold from which the sciences of the Quran and language originated, and because Al-Zajjaj mentioned in his book, after mentioning their evolutionary meanings, which indicates their developmental significance, such as: (its origin is such, and its derivation is such, and in language it is such, and its origin in the language is such)... And so, for these reasons, the title of the research was labeled
Keywords: Al-Zajjaj, semantic development, original meaning of the pronunciation